2018
DOI: 10.1371/journal.pone.0202263
|View full text |Cite
|
Sign up to set email alerts
|

Trans-chalcone increases p53 activity via DNAJB1/HSP40 induction and CRM1 inhibition

Abstract: Naturally-occurring chalcones and synthetic chalcone analogues have been demonstrated to have many biological effects, including anti-inflammatory, anti-malarial, anti-fungal, and anti-oxidant/anti-cancerous activities. Compared to other chalcones, trans-chalcone exhibits superior inhibitory activity in cancer cell growth as shown via in vitro assays, and exerts anti-cancerous effects via the activation of the p53 tumor suppressor protein. Thus, characterization of the specific mechanisms, by which trans-chalc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…In previous studies conducted by our group, chalcone with unsubstituted rings A and B had potent antiproliferative and proapoptotic activities 18 . However, its low solubility in water enables limited additional pharmacological assays, mainly in vivo experiments.…”
Section: Antiproliferative Activity Of Chalcones 1-20mentioning
confidence: 83%
See 1 more Smart Citation
“…In previous studies conducted by our group, chalcone with unsubstituted rings A and B had potent antiproliferative and proapoptotic activities 18 . However, its low solubility in water enables limited additional pharmacological assays, mainly in vivo experiments.…”
Section: Antiproliferative Activity Of Chalcones 1-20mentioning
confidence: 83%
“…Iftikhar et al reported that chalcone bearing chlorine at position 2 was effective against breast cancer cells (CAL-51 line) and induced accumulation of p53 protein 17 . Silva and coauthors described unsubstituted chalcone increased p53 protein activity in osteosarcoma cells (U2OS line) through the induction of heat shock protein DNAJB1 18 .…”
Section: Introductionmentioning
confidence: 99%
“…However, Dos et al reported that series of chalcones with halogens on ring B and additional benzene rings ( 47 IC 50 : 13.2–34.7 μM, Figure 11 ) showed antiproliferative activity against breast cancer cells (MCF-7 and MDA-MB-231), with upregulation of p53 and showed no effect on Sp1 protein expression [ 129 ]. Further mechanistic studies demonstrated that TChal could bind and degrade chromosome region maintenance 1 (CRM1), a nuclear export receptor involved in the active transport of tumor suppressors, and increase heat-shock protein 40 (HSP40) expression in U2OS osteosarcoma cells; the interaction of HSP40 with MDM2 blocked MDM2-mediated ubiquitination of p53, leading to the enhanced stability and activation of p53 [ 128 , 130 ]. Moreover, Siqueira et al reported that TChal could reestablish the p53 pathway and prevent the overexpression of Wnt/β-catenin tumor development, inducing autophagy-related cell death and decreasing the metastatic capacity of HCC HuH7.5 cells [ 131 ].…”
Section: Representative Mechanisms Of Anticancer Action Of Chalconesmentioning
confidence: 99%
“…However, in a phase I clinical trial LMB was found to have severe toxicities and therefore its clinical use was discarded (Newlands et al 1996 ). Other inhibitors such as the aromatic ketone Trans-chalcone (Silva et al 2018 ) and CBS9106 (Sakakibara et al 2011 ) were developed, but none of these candidates reached clinical practice so far.…”
Section: Discussionmentioning
confidence: 99%